Sustainable Economics in Achieving Sustainable Development Goals - Kasiviswanathan, Dr. Ram (Global journal of Business and Integral Security, 2024)
Sustainable economics and the Sustainable Development Goals (SDGs) are intertwined concepts, where economic activity meets the long-term needs of society and the planet. Sustainable development cannot be achieved without addressing inequalities. Sustainable economic policies should focus on creating decent work opportunities, promoting fair trade practices and empowering marginalized communities. Ultimately, achieving the SDGs requires a global shift towards sustainable economic models. Governments, businesses and individuals all have a role to play in creating a more sustainable future. In this article, we will examine Income Taxation on the corporate sector in India from a perspective of sustainability and equal distribution of Income. We will use a recently conducted research by the author to substantiate the recommendations.